1997
DOI: 10.1002/(sici)1096-9926(199703)55:3<185::aid-tera3>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and induced alterations in the cardiac membranous ventricular septum of fetal, weanling, and adult rats

Abstract: Alterations of the cardiac membranous ventricular septum were studied using macrodissection, scanning electron and light microscopy of fetal, weanling, and adult Sprague-Dawley rats. Membranous ventricular septal defects (VSDs) were observed in 2.0% of fetuses on day 21 postcoitus (pc) but not in weanling or adult rats. The most common observation was a nonpatent depression in the membranous septum with an incidence of 38.1, 10.5, 4.3% for fetuses on days 17, 19, or 21 pc, respectively, 11.8% for weanlings, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
1
33
1
Order By: Relevance
“…Trimethadione is a potent inducer of heart malformations in humans and a number of experimental animal models (Feldman et al, ; Rischbieth, ; Veuthey et al, ; Solomon et al, ; Fleeman et al, ). It is believed that dimethadione, the N‐demethylated metabolite of trimethadione, is the proximate teratogen (Buttar et al, ; Wells, ) and we have previously demonstrated that direct administration of DMO induces a number of cardiac malformations including both membranous and muscular VSDs, outflow tract anomalies, and “sponge‐like” myocardium, which would be anticipated to impair cardiac function both in utero and postnatally (Weston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Trimethadione is a potent inducer of heart malformations in humans and a number of experimental animal models (Feldman et al, ; Rischbieth, ; Veuthey et al, ; Solomon et al, ; Fleeman et al, ). It is believed that dimethadione, the N‐demethylated metabolite of trimethadione, is the proximate teratogen (Buttar et al, ; Wells, ) and we have previously demonstrated that direct administration of DMO induces a number of cardiac malformations including both membranous and muscular VSDs, outflow tract anomalies, and “sponge‐like” myocardium, which would be anticipated to impair cardiac function both in utero and postnatally (Weston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1H,K), the area of the membranous portion was small and therefore, the detection of VSD was more difficult. However, when the membranous portion was widely expanded, the depression (Solomon et al . 1997) in this portion was shallow; therefore, VSD was detected easily in the Mg/FT fetuses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, environmental and genetic factors seem to be involved. VSD is found in rat fetuses or chick embryos treated with trimetadione, typan blue and prenalterol (Bruyere et al 1983;Solomon et al 1997), indicating that one of mechanisms for VSD induction might be related to an increase of cAMP level. On the other hand, genetic breeding studies have demonstrated a close correlation between multiple genetic determinants and induction of VSD in two inbred animal sub-lines (Fox 1967(Fox , 1969Kuribayashi et al 1990Kuribayashi et al , 1991 as well as Long-Evans rats (Fox 1967), brown Leghorn chickens (Siller 1958), and keeshonden (Patterson et al 1974).…”
Section: Discussionmentioning
confidence: 99%